Tracking The Eyes Using Interdependence Mean Shift Tracking Algorithm With Appropriate Information Provided - Mat Ibrahim, Masrullizam; Ahmad Radzi, Syafeeza; John, Soraghan (Asian Research Publishing Network (ARPN), 2016)
-